ANALISIS KUALITAS PELAYANAN TERMINAL BANDAR UDARA SENTANI BERDASARKAN KEPUASAN PENUMPANG - An'Nisa Fath Tanar Renngur; Elnia Frisnawati, S.Pd., M.M (Pusat Riset dan Inovasi Nasional, 2022)
One of the services at Sentani Airport is service at the departure and arrival terminals which are handled by TIS (Terminal Inspection Service) officers. This unit is tasked with carrying out inspections of operational support facilities in the curbside area, RPA, and passenger waiting rooms that have been provided by the airport manager. This study aims to determine how big the influence of service quality on passenger satisfaction at Sentani airport and how big the level of passenger satisfaction with services at Sentani airport. The research was conducted on September 02-October 29, 2021 at Sentani Airport, this research is a quantitative study, the population in this study were passengers at Sentani Airport where the passengers had experienced the facilities at the departure terminal and arrival terminal, while the sample in this study this is 100 respondents. The data collection technique used a questionnaire/questionnaire and observation. This study has one variable consisting of the independent variable service quality (X) and the dependent variable passenger satisfaction (Y). Data collection using simple linear regression analysis through SPSS. The results showed that H0 was rejected and Ha was accepted, which means that there is a significant influence between the quality of terminal services at Sentani Airport based on passenger satisfaction with the t-test results found to be 0.000, which means the value is significantly less than 0.05 (0.000 <0.05). The results of the R2 test found that service quality affects passenger satisfaction, which is 0.646. So this means that service quality affects passenger satisfaction by 64.6% and in the category of a strong correlation and the remaining 35.4% is influenced by other variables.